Loyalty as Affecting Mediator of Service Quality And Customer Satisfaction Towards Competitive Advantage - Mohammad Hamim Sultoni; Sudarmiatin Sudarmiatin (MBIA, 2021)
When preparing an effective marketing strategy, a bank must consider its competitors as well as its customers. Establishing a mutual relationship with customers requires a better means of satisfying customer needs than the competitors. Micro, Small, and Medium-sized Enterprises (MSMEs) should always analyze their competitors and develop marketing strategies that effectively give the company a good position compared to the competitors and provide a competitive advantage as strong as possible. This research was conducted using a quantitative method. The design referred to causal relationship research. The data were then analyzed using the path analysis. Findings showed that customer satisfaction, service quality, and customer loyalty affected the competitive advantage of Sentra Batik Pamekasan. The effect of customer loyalty on the competitive advantage could be viewed from the number of Sentra Batik Pamekasan's customers who decided not to move to other financial institutions (banks). When the company could give better service quality, the customer loyalty and the competitive advantage among financial institutions would get higher. Abstrak Dalam mempersiapkan strategi pemasaran yang efektif, pihak perbankan harus mempertimbangkan pesaingnya dan juga konsumennya. Membangun hubungan antara konsumen yang menguntungkan, memerlukan alat pemuasan kebutuhan konsumen sebagai sasaran yang lebih baik daripada pesaingnya. UMKM harus senantiasa menganalisis pesaing dan mengembangkan strategi pemasaran kompetitif yang secara efektif memposisikan UMKM dalam menghadapi pesaing dan memberikan keunggulan kompetitif sekuat mungkin. Penelitian ini menggunakan metode kuantitatif, jenis penelitian termasuk kategori hubungan kausal sedangkan analisis dalam penelitian ini menggunakan analisis jalur (path analysis). Hasil penelitian menunjukkan bahwa kepuasan konsumen, kualitas layanan, dan loyalitas konsumen mempengaruhi keunggulan bersaing di Sentra Batik Pamekasasan. Dampak dari loyalitas konsumen terhadap keunggulan bersaing dapat dilihat dari seberapa banyak konsumen Sentra Batik Pamekasasan yang tidak pindah ke lembaga keuangan lain. Semakin bagus kualitas layanan maka semakin tinggi tingkat loyalitas konsumen dan keunggulan bersaing antar lembaga keuangan juga akan semakin tinggi. Kata Kunci : Loyalitas konsumen, kepuasan konsumen, kualitas layanan, keunggulan bersaing